Ẓafarnamah: A Glimpse into the Text and its Historical and Intellectual Context - Chamankhah, Leila (International Journal of Islamic Khazanah, 2023)
Ẓafarnāmah (Book of Victory), written by the tenth Sikh leader, Guru Gobind Singh (d. 1708), in 1705, about the Mughal emperor of India, Aurangzeb (d. 1706). It is widely considered evidence of a religious leader's spiritual victory over a tyrant who not only broke his Koranic oath (and, consequently, fell from his status as a good believer). The book, originally in Persian poetry, is composed of one hundred and eight bayts (verses), and the first twelve verses praise God and His power. Due to its bold divine connotations, Ẓafarnāmah is widely regarded as a spiritual text. However, as the researcher will argue in the following, Ẓafarnāmah should not be treated as just a spiritual text but as one of “the mirrors for princes,”whichhas a well-established tradition in the history of Persian literature and a political ethics tradition as well.